Biosystematic studies in the Brazilian endemic genus Hoffmannseggella H. G. Jones (Orchidaceae: Laeliinae): a multiple approach applied to conservation - Verola, Christiano Franco (Universidad de Costa Rica, 2015)
In recent molecular studies, the orchid genus Laelia Lindl. was segregated in two main groups: Laelia (a Mexican/Central American group), and Sophronitis Lindl. (a South American group) (van den Berg et al. 2000, van den Berg & Chase 2000). Later, other studies argued the legitimacy of this classification, suggesting the segregation of the South American group (Sophronitis sensu van den Berg et al. 2000) in four genera: Hadrolaelia (Schltr.) Chiron & V.P. Castro, Hoffmannseggella H.G. Jones, Dungsia Chiron & V.P.Castro, and Microlaelia (Schltr) Chiron & V.P.Castro (Chiron & Castro 2002).